2019
DOI: 10.1111/jocn.14849
|View full text |Cite
|
Sign up to set email alerts
|

Supporting self‐management of radiation‐induced bowel and bladder dysfunction in pelvic‐cancer rehabilitation: An ethnographic study

Abstract: Aims and objectives To describe and understand strategies that oncological nurses use to support self‐management of radiation‐induced bowel and bladder issues in pelvic‐cancer rehabilitation patients. Background Nurse‐led self‐management of radiation‐induced bowel and bladder issues holds the potential to support cancer survivors. Design An ethnographic approach was applied in this study, which adhered to Consolidated Criteria for Reporting Qualitative Research (COREQ) guidelines. Methods Data collection was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In Sweden, promising steps are being taken towards developing a programme for national coordination of cancer rehabilitation practice. Cerna et al , 23 in a study concerning self-management from an educational perspective, observed that patients and nurses can together create tailor-made solutions. The nurses focus on encouraging the patients to self-reflect and on maintaining the patient’s motivation to continue to engage in self-care.…”
Section: Findings To Datementioning
confidence: 99%
“…In Sweden, promising steps are being taken towards developing a programme for national coordination of cancer rehabilitation practice. Cerna et al , 23 in a study concerning self-management from an educational perspective, observed that patients and nurses can together create tailor-made solutions. The nurses focus on encouraging the patients to self-reflect and on maintaining the patient’s motivation to continue to engage in self-care.…”
Section: Findings To Datementioning
confidence: 99%
“…In this regard, surgery cannot benefit patients; thus, chemotherapy is frequently used. As a damaging treatment, chemotherapy can produce strong side effects, making it prone to hair loss, abdominal pain, liver and kidney function damage [ 3 ], and further damaging the body's immune cells to undermine immune function. In addition, up to 65% of patients develop psychological stress reaction during chemotherapy, in the most direct manner of poor psychological state and sleep quality.…”
Section: Introductionmentioning
confidence: 99%